2007
DOI: 10.1161/atvbaha.107.142430
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immune System Activation and Arterial Inflammation Accelerates Atherosclerosis in Lupus-Prone Mice

Abstract: Objective-Premature atherosclerosis is a characteristic feature of systemic lupus erythematosus, a prototypic autoimmune disease. The principle cellular and molecular mechanisms which underlie such accelerated atherosclerosis are indeterminate. Methods and Results-The pathophysiology of lupus-mediated atherogenesis was evaluated in a novel animal model involving transplantation of bone marrow cells from the lupus prone strain gld into Ldl-r Ϫ/Ϫ mice. Diet-induced atherogenesis in lethally-irradiated Ldl-r Ϫ/Ϫ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…9 Moreover, apoptotic cells may possess proinflammatory properties, in part as a result of the presence of oxidized phospholipids (oxPLs) at their surface, 10,11 which are known triggers of inflammatory responses in arterial tissues. 12 In this setting, studies of mice in which components of the apoptotic cell clearance machinery have been deleted 13 or of lupus-prone mice characterized by ineffective apoptotic cell clearance 14 have revealed that defective apoptotic cell clearance is associated with enhanced atherosclerotic plaque progression.…”
Section: Clinical Perspective P 1804mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Moreover, apoptotic cells may possess proinflammatory properties, in part as a result of the presence of oxidized phospholipids (oxPLs) at their surface, 10,11 which are known triggers of inflammatory responses in arterial tissues. 12 In this setting, studies of mice in which components of the apoptotic cell clearance machinery have been deleted 13 or of lupus-prone mice characterized by ineffective apoptotic cell clearance 14 have revealed that defective apoptotic cell clearance is associated with enhanced atherosclerotic plaque progression.…”
Section: Clinical Perspective P 1804mentioning
confidence: 99%
“…The transgene consists of the human hBcl-2 cDNA from pORF-hBcl-2 (InvivoGen, San Diego, Calif) cloned downstream of the mouse macrophage-specific promoter CD68 from pDRIVE-mCD68 (Invivogen All these procedures were performed as previously described 14,16 (see the Methods section in the online-only Data Supplement).…”
Section: Transgenic Animals and Atherosclerosis Studies Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial clinical data on the effects of these inhibitors on glycemic control and other clinical parameters, there is a paucity of data in humans that comprehensively evaluates the whole body metabolic adaptation to pharmacologic inhibition of the renal SGLT2 cotransporter. In this issue of the JCI, results are presented from two elegantly conducted metabolic studies in individuals with T2D that evaluated the SGLT2 inhibitors, dapagliflozin and empagliflozin (6,7). Both studies were well designed, used sophisticated metabolic techniques, evaluated subjects with T2D, involved both acute and longer-term evaluation (two-and four-week observations), and evaluated whole body insulin sensitivity and endogenous hepatic glucose production in response to SGLT2 inhibition.…”
Section: Pharmacological Control Of Hyperglycemiamentioning
confidence: 99%
“…In the study by Merovci et al (6), the primary goal was to evaluate the impact of hyperglycemia and its reduction by SGLT2…”
Section: Testing the Glucotoxicity Hypothesis In Patients With T2dmentioning
confidence: 99%